(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
Leiorreuma nicobarense Pushpi Singh, Jagadeesh and Kr. P. Singh, a new species from Great Nicobar Island, India is described and illustrated. It is characterized by its sessile lirellae with widely exposed densely whitish pruinose disc, inspersed hymenium, 8-spored asci with 6-locular ascospores and presence of stictic, constictic and hypostictic acids. Key to species occurring in India is provided. Keywords: Ascomycota; Lichenized fungi; New species; Taxonomy; Sundaland. Bangladesh J. Plant Taxon. 24(1): 912, 2017 (June)